Thermoanalysis of Smart Heating Textiles for Car Seats - ADAM, NUŠA; POTRČ, MELANI; SLAVINEC, MITJA; ZAVEC, DANIELA; KLEMENČIČ, EVA (Anali PAZU, 2022)
In this paper, we focus on active smart textiles that detect a temperature change and respond to it by turning the heating on or off. In the development of such products, it is important to know the temperature-time dynamics of heating and cooling to control and prevent overheating. Thermoanalysis proves to be an appropriate method. An infrared camera enables a non-contact study of the temperature distribution on the surface of a textile product and the identification of hot spots. We present the results of thermoanalsyis of two samples of heating textiles in combination with two samples of melamine textiles, which is considered a good thermal insulator. In analysis and results interpretation we focus on the possibility of using individual samples of heating textiles and their combinations with melamine for heated car seats.
Keywords: textile products; function heating; heated automotive seats; thermoanalysis; change temperature